Field Cooling Rates of Asphalt Concrete Overlays at Low Temperatures - Eaton,Robert A; Berg,Richard L (1980)
Six overlay test sections were placed on an existing test road in Hanover, New Hampshire, to gain experience in compaction of asphalt pavements at rolling temperatures as low as 150 F. The asphalt cement and aggregated used had mix characteristics similar to those of the mix expected to be used for a proposed overlay project at Thule Air Base, Greenland. Results of the overlay tests showed that computer-modeled cooling curves can be accurate predictors of the actual asphalt overlay cooling with time. In addition, the effects of temperature upon compaction were determined and its was found that nuclear gauges, when used and calibrated properly, successfully monitored mix density changes during compaction. (Author)